PEMBELAJARAN MATEMATIKA DENGAN STRATEGI ICARE BERACUAN KONSTRUKTIVISME UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATERI DIMENSI TIGA (Universitas Negeri Semarang, 2012)
Penelitian ini bertujuan untuk: (1) menghasilkan perangkat pembelajaran matematika berupa silabus pembelajaran (SP), rencana pelaksanaan pembelajaran (RPP), lembar kegiatan siswa (LKS), modul siswa (MS), dan tes kemampuan berpikir kreatif (TKBK) yang valid, (2) memperoleh perangkat pembelajaran yang praktis, dan (3) tercapainya pembelajaran matematika yang efektif. Penelitian ini mengacu pada model pengembangan Plomp dengan tahapan: investigasi awal; desain; realisasi/konstruksi; tes, evaluasi dan revisi; dan implementasi. Uji coba perangkat pembelajaran dilakukan pada siswa SMA Negeri 2 Kudus kelas X-5 sebagai kelas ICARE dan kelas X-3 sebagai kelas Ekspositori. Data diambil dengan lembar validasi, pengamatan, angket dan tes. Data diolah dengan uji ketuntasan, regresi, banding, dan peningkatan kemampuan berpikir kreatif. Hasil penelitian menunjukkan: (1) rata-rata skor SP, RPP, LKS, MS, dan TKBK lebih dari 4,00 menunjukkan kriteria valid, (2) respon siswa dan guru terhadap komponen dan kegiatan pembelajaran positif, (3) pembelajaran matematika dengan strategi ICARE beracuan konstruktivisme efektif. Efektivitas ditandai dengan: (a) jumlah siswa yang nilai prestasi belajarnya > 73 mencapai 93,33%, (b) motivasi belajar siswa dan aktivitas siswa berpengaruh sebesar 51,9% terhadap kemampuan berpikir kreatif, (c) rata-rata prestasi belajar kelas ICARE sebesar 81,33 sedangkan kelas Ekspositori 58,70, dan (d) kemampuan berpikir kreatif siswa meningkat dari rata-rata nilai pre-tes 28,27 menjadi pos-tes 81,33.The aims of this study are: (1) to describe the characteristics of the learning models of Komeks to meet the needs of the teacher of elementary school, (2) to describe the characteristics of the learning model of Komeks to meet the needs of the students, (3) to describe the principle of the learning models of Komeks, (4) to develop prototype of guidelines of the learning model using Komeks, and (5) to determine the model effectiveness of Komeks involving the values of character education in reading intentive aspect in elementary school. Research and development approaches are employed in this research derived from Borg and Gall (1983). The steps are; (1) collecting information and theoretical reviews, (2) desigining the development model, (3) collecting main data in the field, (4) analysing primary data, (5) composing development model, (6) validation, and (7) effectiveness trial. The resource of the data consists of teachers and students of class VI elementary school and the expert of learning model and linguists. The data employes descriptive qualitative and quantitative method. The research aims to: (1) produce the math learning materials in the form of syllabus (SP), study plan (RPP), student work (LKS), student modules (MS), and test to have a creative thinking (TKBK) which are valid; (2) formulate the learning materials which are practical and, (3) to have an effective math learning. This research refers to the Plomp development model with several stages; desigining, realizing/constructing; test, evaluation, and revision, and implementation. The material for prototype learning 1 is validated and revised according to validator inputs. Hence, the prototype 2 is then applied in a experimental class. After that, it will be finalised as prototype 3. The subjects of the study are students of senior high school state of 2 Kudus class X consisting of eight classes. X-5 is chosen as has been randomly selected. It is callsed ICARE. And class X-3 is called expository. The validation sheet, observatiob, questioner, and test are used. It is then processed through test, regression, comparative test, and creative thinking test. The result shows that : (1) after the validation from the expert and the peers, the scores are SP 4,233, RPP 4,150, LKS 4,080, MS 4,140, TKBK 4,200 which proved their validity. (2) the response of the students and the teachers are found to be positive, (3) math learning using strategy ICARE referred to constructivism is effective. It is shown by: (a) the students performance > 73 (KKM) reached 93,33%, (b) the students motivation in studying and their activities play vital roles as much as 51,9% towards the creative thinking, (c) the average of the students achievement in class ICARE is 81,33 > with the average of the Ekspocitory is 58,70, and (d) the ability of creative thinking increases from 28,27 in pre-test to 81,33 in post test. It is suggested that the math learning using ICARE based on constructivism can be developed in other math materials.